2018
DOI: 10.1017/s1047951118001233
|View full text |Cite
|
Sign up to set email alerts
|

Communication and decision-making regarding children with critical cardiac disease: a systematic review of family preferences

Abstract: Critical heart disease in the pediatric population is associated with high morbidity and mortality. Research around the most effective communication and decision-making strategies is lacking. This systematic review aims to summarise what is known about parent preference for communication and decision-making in children with critical heart disease. Database searches included key words such as family, pediatric heart disease, communication, and decision-making. A total of 10 studies fit our inclusion criteria: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Many previous studies have focused on parent perspectives on shared decision-making and communication. 9,20,21 While we found that providers perceived a discrepant parental focus on short-term compared to the providers' emphases on long-term outcomes, previous work has highlighted parents' desire for more information related to long-term outcomes. Further, Arya et al found that parents rated information on quality of life as significantly more important than providers did.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Many previous studies have focused on parent perspectives on shared decision-making and communication. 9,20,21 While we found that providers perceived a discrepant parental focus on short-term compared to the providers' emphases on long-term outcomes, previous work has highlighted parents' desire for more information related to long-term outcomes. Further, Arya et al found that parents rated information on quality of life as significantly more important than providers did.…”
Section: Discussioncontrasting
confidence: 51%
“…The nuances of CHD diagnoses and statistics related to outcomes can be difficult to convey at baseline and exacerbated if there are language, literacy, or numeracy barriers. Balancing the details versus the big picture can be challenging since parents have previously expressed a desire for more information than clinicians may provide, 9,22 with the caveat that the amount of information can be overwhelming and requires repetition. Previous work has found that the amount and manner in which this information is conveyed may be related to provider subspecialty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation